MENGINGAT KEMBALI PEMIKIRAN ABDUL MUKTI ALI: PENDEKATAN SCIENTIFIC-CUM-DOCTRINAIRE DAN KONSEP AGREE IN DISAGREEMENT - Hayati, Siti Muna (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2017)
This biographical reseach is talking about A. Mukti Ali, a moslem intellectual from Cepu. He is the founder of scientific-cum-doctrinaire approach or synthetic method, which is one of Islamic Studies approaches. He is also known as the founder of religious harmony concept in Indonesia, that is agree in disagreement. He also opened Comparative Religion department in 1960 so that the Comparative Religion becoming well-known in Indonesia.